Fuel substitution possibilities, factor productivity, and technological progress in the industrial sector of India - Raza, Muhammad Yousaf; Lin, Boqiang; Javed, Qasim (Frontiers in Sustainable Energy Policy, 2024)
India is often referred to as the next development superpower and is generally seen as an efficient goal for a large-scale industrialization center. This paper has tried to investigate the output elasticity, substitution elasticity and technological advancement between the various factors (i.e., labor, capital and energy use) in the industrial sector of India. To investigate the factor’s productivity, a trans-log production function was applied; however, ridge regression was used to analyze the various parameters to check the multicollinearity issue. The results show that: (i) analyzed inputs are optimistic and show an increasing return to scale average of 1.18, 1.41 and 1.24 between labor, capital and energy. (ii) The pairs substitution between labor-industrial energy utilization and capital-industrial energy consumption are found to be 0.96 and 0.98 on average, presenting that capital, labor and energy are good substitutes that need more attention in the production process. (iii) The technological progress between factors ranges from -0.4 to +0.02, in which labor-energy and capital-energy provide quicker outcomes than capital and labor. Finally, the industrial sector can attain maximum productivity if capital and skilled labor are improved under the sustainable development goals because energy and capital are presenting maximum unity. Finally, energy substitution and low-carbon technological efforts can be better fit for attaining dual-carbon goals in the industrial sector.